Impacts of COVID-19 on Tourism Industry in Famagusta, Northern Cyprus - Jafari, Kaveh (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The study sought to examine the impacts of COVID -19 on tourism in the case of Famagusta town, in North Cyprus. Via a qualitative research approach, data is collected through face-to-face interviews from direct and indirect tourism stakeholders operating in Famagusta. Famagusta one of the largest towns in North Cyprus is a attractive tourist destination, boasting some of the best pristine beaches for sun, sea and sand experience as we well as interesting historical sites. A judgmental sampling strategy was employed to collect data from tourism stakeholders on the impacts of COVID-19 on tourism. Descriptive data analysis is engaged to report the results. Results of the study showed that, the novel corona virus has hampered on the tourism sector in Famagusta, North Cyprus. Indeed, as the globe suffered its effects in terms of economic gains, business and business closure. It has been the same with Famagusta, while a few private sectors positively gained (Internet and Technology), all other tourism reliant sectors such as hotels, restaurants, travel agencies and the transport sector massively suffered as a result of the global lockdown due to COVID 19 pandemic. And, although restrictions have been eased off and it is back to business again, work has not been the same again. Evidently customers are less and there is reduced travel and tourist arrivals in the country. Tourism is an essential sector in the town and country at large, as such practical implications encourage all stakeholders to actively endorse precautionary measures in business. Furthermore, recommendations to ensure vaccines and strict quarantine measures are affected were made in thus study. Keywords: Tourism Planning, Covid-19 Impacts, Pandemics

ÖZ: Çalışma, Kuzey Kıbrıs'ın Gazimağusa kasabası örneğinde COVID-19'un turizm üzerindeki etkilerini incelemeyi amaçladı. Nitel araştırma yaklaşımı ile veriler, Gazimağusa'da faaliyet gösteren doğrudan ve dolaylı turizm paydaşlarından yüz yüze görüşmeler yoluyla toplanmaktadır. Kuzey Kıbrıs'ın en büyük şehirlerinden biri olan Gazimağusa, güneş, deniz ve kum deneyimi için en iyi el değmemiş plajlardan bazılarının yanı sıra ilginç tarihi yerlere sahip çekici bir turizm merkezidir. Turizm paydaşlarından COVID-19'un turizm üzerindeki etkileri hakkında veri toplamak için yargılayıcı bir örnekleme stratejisi kullanıldı. Sonuçları rapor etmek için açıklayıcı veri analizi yapılır. Çalışmanın sonuçları, yeni korona virüsün Kuzey Kıbrıs'ın Gazimağusa kentinde turizm sektörünü engellediğini gösterdi. Nitekim, dünya ekonomik kazanımlar, iş ve işlerin kapanması açısından etkilerini yaşarken. Gazimağusa ile aynı durumdayken, birkaç özel sektör olumlu bir şekilde kazanırken (İnternet ve Teknoloji), oteller, restoranlar, seyahat acenteleri gibi diğer tüm turizme bağımlı sektörler ve ulaşım sektörü nedeniyle küresel kilitlenme nedeniyle büyük zarar gördü. Kovid-19 ve kısıtlamaların azaltılmasına ve tekrar faaliyete geçmesine rağmen, işler bir daha eskisi gibi olmadı. Anlaşılan, müşteriler daha az ve ülkeye seyahat ve turist girişleri azaldı. Bu tür pratik uygulamalar tüm paydaşları iş dünyasında ihtiyati tedbirleri aktif olarak kabul etmeye teşvik ettiğinden, turizm şehir ve ülke genelinde önemli bir sektördür. Ayrıca, bu çalışmada aşıların ve sıkı karantina önlemlerinin etkilenmesini sağlayacak öneriler yapılmıştır. Anahtar Kelimeler: Turizm Planlaması, Covid-19 Etkileri, Pandemiler
Master of Science in Tourism Management. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Tourism, 2021. Supervisor: Asst. Prof. Dr. Ali Özduran.
Keywords: Tourism; Tourism--Hospitality Industry--COVID 19 Pandemic--Cyprus (Turkish Republic of Northern Cyprus, 1983-); COVID 19 Pandemic--Tourism--Travel--Hospitality industry; Effects of COVID 19--Tourisml Industry--Hotels--Famagusa--Cyprus (Turkish Republic of Northern Cyprus, 1983-).; COVID-19--Economic aspects--Cyprus (Turkish Republic of Northern Cyprus, 1983-).; COVID-19 Pandemic, 2020-; COVID-19 (Disease)--Economic aspects; Tourism Planning; Covid-19 Impacts; Pandemics